Customers Bargaining Power and its Impingements on Market Share of Firms’ in the Nigerian Beverage Industry - S. Adeleke, Bamidele; Ozioma Obi-Anike, Happiness; Nkiruka Okafor, Chikodili (International Journal of Psychosocial Rehabilitation, 2020)
This study investigates the impingement of customers bargaining power on the market share of beverages firms in Nigeria. Across-sectional survey design method was adopted with self-administered questionnaires that were used to gather data from respondents who were management and non-management staff of three selected beverages companies in Oyo and Ogun states Nigeria. Sample size of four hundred and seventy-one respondents was drawn from the population. Having tested the formulated hypothesis using person product moment correlation at 0.05 significance level, the finding revealed that there is a significant positive relationship between customers bargaining power and the market share of beverages firms in Nigeria. Informed by this finding, the study recommended that Nigerian beverages firms need to be committed to maintaining a cordial relationship with their customers and avoid possible conflict in both short and long-run. The firms also need to professionally maintain the synergy between itself and the customers so as to enjoy competitive advantage over other rivals.